Educational differences in acute infectious diseases in the Netherlands: results from a nationwide health survey. (25th January 2020) - de Gier, Brechje; Houben - van Herten, Marieke; Uiters, Ellen; Hahné, Susan J M
Abstract: Background: It is unclear to what extent socioeconomic inequalities exist in common infectious diseases in high-income countries. We aimed to explore educational differences in five common acute infectious diseases in adults in the Netherlands. Methods: As part of a year-round repeated cross-sectional health survey, adults aged 25 and older were asked if they had experienced acute upper or lower respiratory tract infections, acute otitis media, urinary tract infections or gastro-enteritis in the two previous months. If so, participants were asked whether they had consulted their general practitioner and if they had been unable to perform their normal daily activities. These outcomes were analyzed per highest attained level of education. Results: Data of 18 629 survey respondents were used in the analyses. People with a low educational level had lower odds of upper respiratory tract infections (OR 0.88, 95% CI 0.81–0.95), but higher odds of lower respiratory tract infections (OR 1.57, 95% CI 1.16–2.11). After adjustment for several covariates, the differences in upper respiratory tract infections remained statistically significant (aOR 0.84, 95% CI 0.77–0.91). The educational differences in lower respiratory tract infections were mitigated by adjusting for chronic diseases and health behaviours. For all infectious diseases, the likelihood of general practitioner consultation was highest for the lower educated group. Inability to work or perform normal daily activities due to an infectious disease was similar across all levels of education. Conclusion: This study shows that educational differences in incidence and care seeking behaviours exist for common acute infectious diseases in the Netherlands.